2008
DOI: 10.1016/j.aquatox.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation and sulfonation, in vitro, of the major endocrine-active metabolites of methoxychlor in the channel catfish, Ictalurus punctatus, and induction following treatment with 3-methylcholanthrene

Abstract: The organochlorine pesticide, methoxychlor (MXC), is metabolized in animals to phenolic monoand bis-demethylated metabolites (OH-MXC and HPTE respectively) that interact with estrogen receptors and may be endocrine disruptors. The phase II detoxication of these compounds will influence the duration of action of the estrogenic metabolites, but has not been investigated extensively. In this study, the glucuronidation and sulfonation of OH-MXC and HPTE were investigated in subcellular fractions of liver and intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…For example, subcellular fractions from the channel catfish liver and intestine were used to study the fate of methoxychlor, a pesticide shown to cause reproductive effects in fish. Methoxychlor was readily de‐methylated by microsomal cytochrome P450 to estrogenic metabolites [85], but the demethylated metabolites were much more slowly glucuronidated and sulfonated, suggesting the demethylated metabolites would bioaccumulate in the catfish [86]. Assuming other fish biotransform methoxychlor similarly to the channel catfish, these studies show why fish exposed to methoxychlor experience reproductive effects.…”
Section: In Vitro Techniques For Assessing Bioaccumulation In Fishmentioning
confidence: 99%
“…For example, subcellular fractions from the channel catfish liver and intestine were used to study the fate of methoxychlor, a pesticide shown to cause reproductive effects in fish. Methoxychlor was readily de‐methylated by microsomal cytochrome P450 to estrogenic metabolites [85], but the demethylated metabolites were much more slowly glucuronidated and sulfonated, suggesting the demethylated metabolites would bioaccumulate in the catfish [86]. Assuming other fish biotransform methoxychlor similarly to the channel catfish, these studies show why fish exposed to methoxychlor experience reproductive effects.…”
Section: In Vitro Techniques For Assessing Bioaccumulation In Fishmentioning
confidence: 99%
“…About four times higher efficiency was observed in the intestinal microsomes of I. punctatus for the glucuronidation of mono-O-demethylated methoxychlor than in the hepatic ones, while cytosolic sulfonation of the di-O-demethylated metabolite proceeded at two times higher efficiency in the liver than in the intestine. 85) Significantly higher GST activity of this species against CDNB was observed in the liver than in the gills, and in the respective cytosol than in the microsomes. 86) As a result, more conjugates of chlorothalonil with GSH were formed in the hepatic cytosol.…”
Section: Salinitymentioning
confidence: 87%
“…54,55) These results show the usefulness of hepatocytes and liver slices to qualitatively estimate the in vivo metabolism of methoxychlor. In vitro studies using the hepatic microsomes (+ UDPGA) and cytosol (+ PAPS) of I. punctatus showed a formation rate of glucuronide conjugate ten-times higher than the sulfate one from the Odemethylated metabolite, 85) which partly explains the detection of glucuronides as dominant components in the bile and liver of the force-fed fish. 138) 3.1.3.…”
Section: Pesticidesmentioning
confidence: 98%
“…Please note that throughout the manuscript and in an effort to simplify, genes appear in italicized lower case letters and proteins appear in upper case letters. The liver was investigated because it is the major site for detoxification of compounds such as MXC and its metabolites (James et al, 2008) and is the site for the synthesis of VTG prior to translocation to the ovaries for incorporation into the eggs. Therefore, the liver has a major role in the normal reproductive process of female teleost fish of many egg-laying species and the liver can be responsive to estrogens in males after exposure by producing VTG.…”
Section: Methodsmentioning
confidence: 99%